Using stents in the management of malignant bowel obstruction: the current situation and future progress. (3rd July 2017) - Fugazza, Alessandro; Galtieri, Piera Alessia; Repici, Alessandro
ABSTRACT: Introduction : The use of self-expanding metal stents (SEMS) has been considered an effective and safe alternative to emergency surgery as bridge to surgery or for palliation in advanced colorectal cancer even though more recent data have raised concerns on both early and long-term outcomes when patients are treated with bridge to surgery indications. Areas covered : A comprehensive literature review of articles on endoscopic management of malignant bowel obstruction was performed. Indication, technique, outcomes, benefits and risks of these treatments in acute malignant colonic obstruction were reviewed. The clinical effectiveness and safety of SEMS in obstructive colorectal cancer, as bridge to surgery or for palliation compared to surgery, is discussed. Expert commentary : SEMS placement, when performed in tertiary level center with appropriate expertise in colorectal stenting, may have several advantages over surgery avoiding the potential for surgical morbidity in a typically frail group of patients even though these advantages are to be carefully balanced over the risk of life-threatening, stent-related complications.